An Audit on Did Not Attend (DNA) Rate in the Learning Disability Outpatient Mental Health Setting, BCHFT - Ayesha Fazal ur Rehman; Joseph Vella (BJPsych Open)
Aims: Service users not attending outpatient clinics without prior notification are considered as DNA. We intended to identify the factors contributing to DNA in ID patients, with a view to mitigate the risks and safeguarding concerns associated with it and also to assess staff compliance with the Trust’s DNA policy.